An Empirical Analysis of Factors Affecting Renewable Energy Consumption in Association of Southeast Asian Nations-4 Countries - Kumaran, Vikniswari Vija; Ridzuan, Abdul Rahim; Khan, Farman Ullah; Abdullah, Hussin; Mohamad, Zam Zuriyati (International Journal of Energy Economics and Policy, 2020)
This study aimed to explore the determinants of renewable energy consumption in selected ASEAN countries by emphasizing the significant role played by the quality of governance. This paper is classified according to the coverage of three dimensions approach (economic, environment, and governance) for sustainability. This study employed panel data analysis to examine the relationship between GDP, CO2 emissions, FDI, trade openness, urbanization, and quality of governance on renewable energy consumption in selected ASEAN countries from 1990 to 2016. The results revealed that urbanisation has a significant positive impact on renewable energy based on FMOLS and DOLS analyses while the quality of governance has a significant positive impact on renewable energy based on PMG analysis in the long run. However, GDP and trade openness have a significant negative impact on renewal energy. The elasticity analysis in the short run revealed that none of the factors applied in this study affected renewable energy consumption. Hence, several policies are recommended as an excellent approach to meet the energy demand of private investors and future generations. Keywords: Renewable Energy, ASEAN, Quality of Governance, Panel Estimation JEL Classifications: F64, Q42, P28 DOI: https://doi.org/10.32479/ijeep.8142